1971
DOI: 10.1042/cs0400197
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Sympathetic Control of Normal and Diseased Synovial Blood Vessels: The Effect of α and β Receptor Stimulation and Inhibition, Monitored by the 133Xenon Clearance Technique

Abstract: S U M M A R Y1. The half-life (T+) of the disappearance curve of 133Xe from the knee joint has been used as an indirect measure of synovial perfusion.2. The effects of intra-articularly administered isoprenaline and noradrenaline and their respective blocking agents, propranolol and phentolamine, on the T+ values have been investigated in normal subjects and in patients with osteoarthritis and rheumatoid arthritis.3. In normal subjects isoprenaline increased the clearance rate and this effect was blocked by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…This discrepancy may be due to different substances being used to induce inflammation and/or the longer time course of inflammation (24 h) in this study. Our results are more in agreement with the findings of Dick, Jubb, Buchanan, Williamson, Whaley & Porter (1971), in which they observed loss of constrictor tone of blood vessels in chronically inflamed human joints. Although highly correlated with blood flow, the proportionality of change in P3°2 compared with blood flow was dissimilar (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy may be due to different substances being used to induce inflammation and/or the longer time course of inflammation (24 h) in this study. Our results are more in agreement with the findings of Dick, Jubb, Buchanan, Williamson, Whaley & Porter (1971), in which they observed loss of constrictor tone of blood vessels in chronically inflamed human joints. Although highly correlated with blood flow, the proportionality of change in P3°2 compared with blood flow was dissimilar (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Previous investigations have revealed the role of the sympathetic nervous system in normal and inflamed knee JBF regulation [6,8,22] showing a significant reduction in constrictor response to nerve stimulation by the process of inflammation. Bloodvessel response to saphenous nerve stimulation in the rat was also shown to be reduced in chronically inflamed knee joints [15].…”
Section: Discussionmentioning
confidence: 99%
“…A high correlation has been found between synovial fluid PO 2 and synovial blood flow in both normal and acutely inflamed rabbit knee joints [22], suggesting the importance of joint blood flow (JBF) regulatory mechanisms in supplying oxygen and other nutrients to the synovial tissues. Using the 133 Xe clearance technique, Dick et al [6] obtained evidence for a contribution from both α-and β-adrenergic mechanisms to the regulation of blood flow in normal and diseased human articular vascular beds. Our previous studies showed a significant reduction in the efficacy of the sympathetic nervous system in regulating blood flow to the inflamed joint [22], which may account for the significantly higher blood flow observed in this condition.…”
Section: Introductionmentioning
confidence: 98%
“…Intra-articular administration of isoprenaline results in a marked increase in the clearance rate of 133 Xe from diarthrodial joints (Dick et al 1971a). In contrast, the clearance rate is markedly decreased, when norepinephrine is administered.…”
Section: Synovial Vascular Bedmentioning
confidence: 98%